Crucial leadership competencies of school heads in effective school management: a comprehensive systematic review - Ambon, Josephine; Alias, Bity Salwana; Mansor, Azlin Norhaini (Journal of Education and Learning (EduLearn), 2025)
This article explores the essential leadership competencies of school heads required for effective school management. The article provides a comprehensive overview of leadership competencies as a key supporter in enhancing effective school management. This study used preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach by analyzing 756 publications from 2019 to 2023 through the Scopus, Web of Science (WoS), and Eric databases. The data were collected, reviewed, and underwent a peer-review process before a systematic literature review. The expected results uncovering a set of crucial leadership competencies that are paramount in navigating the multifaceted responsibilities of school heads. These competencies encompass strategic vision, effective communication, adept decision-making, team collaboration, and adaptability to dynamic educational landscapes. The final finding data is (n=31) which review identified key themes including the leadership competencies and the roles of school heads in effective school management. The findings are divided into three themes which is: i) principals' leadership and professional development, ii) challenges and coping strategies in school leadership, and iii) leadership styles and cultural considerations. In conclusion, this article indicates the significance of leadership competencies in the effective management of schools. The insights derived from this research serve as a valuable resource for teachers, school heads, and policymakers aiming to elevate the quality of education.